Digital Platform Strategy: A Theory Primer with Selected Conceptual Add-ons - Gert Bruche (Berlin School of Economics and Law (HWR Berlin), Berlin Professional School (BPS), 2022)
This primer is intended to serve as a background text for a 'platform chapter' in Bachelor or Master level courses on Strategic Management. While the 'traditional firm' can be described as a value-adding chain (Pipeline), platform businesses 'invert' production and consumption to the outside and in essence 'manufacture' transactions. The constitutive drivers of the platform competition and the platform economy are network effects which come in different types and varying geographic reach. There is a very wide variety of different types of platform businesses, however on a fundamental level it makes sense to distinguish transaction (exchange) and innovation (maker) platforms. 'Platform strategy analysis' is still at an early stage, it is focused on 'single platforms', and it is still a 'moving target'. The large dominant players like Google, Amazon, Microsoft, Apple and others expand and defend their dominant positions through complex 'multi-platform strategies'. Early-stage platform Start-ups on the other hand must overcome the 'chicken-or-egg' problem with various strategies and tactics. In the internationalization strategy of platforms two archetypes, country-by-country (or multidomestic) and global (globally integrated) strategies, prevail in platform markets. There is a need for platform regulation by governments and the EU in five different domains: antitrust policy, publishing (hate speech, fake news), data ownership/privacy, labour market, tax avoidance. – – Das Paper ist als Hintergrundtext für ein Plattformkapitel in Bachelor oder Masterkursen zu 'Strategischem Management' intendiert. Das 'traditionelle Unternehmen' kann als Wertschöpfungskette (Pipeline) verstanden werden (mit Inputs, die über verschiedene Stufen zu Outputs verarbeitet werden). Plattformunternehmen dagegen externalisieren Produktion und Konsumtion und 'produzieren' vor allem Transaktionen. Konstitutive Treiber des Plattformwettbewerbs sind Netzwerkeffekte verschiedener Art und mit unterschiedlicher räumlich-geographischen Reichweiten. Es gibt eine große Vielfalt verschiedener Typen von Plattformunternehmen, ganz grundsätzlich kann man aber Transaktions- (Austausch-) und Innovations- (Produzierende-) Plattformen unterscheiden. Die Strategieanalyse von Plattformen ist immer noch in einem frühen Stadium, sie ist fokussiert auf die isolierte Betrachtung einzelner Plattformen und unterliegt ständigen Veränderungen. Die großen Plattformspieler wie Google, Amazon, Microsoft, Apple und andere expandieren und verteidigen ihre dominante Position durch komplexe 'Multi-Plattformstrategien'. Plattformen in der Start-Up Phase müssen das 'Henne-Ei-Problem' mit verschiedenen Strategien und Taktiken überwinden. Hinsichtlich der Internationalisierung von Plattformunternehmen lassen sich zwei Archetypen unterscheiden, Land-für-Land (oder multilokale) und globale (global integrierte) Strategien. Notwendige Regulierungsmaßnahmen seitens der Regierungen und der EU betreffen fünf verschiedene Bereiche: Wettbewerb und Kartellrecht, Veröffentlichung und Medien (Hassrede, Falschnachrichten), Datenschutz, Arbeitsmarktregulierungen und Steuervermeidung- oder -hinterziehung.
Keywords: 330